Multisystem Abdominal Trauma in Pregnancy: Multidisciplinary Approach to Diagnosis and Treatment - V. V. Aleksandrov; N. A. Burova; S. S. Maskin; V. V. Matyukhin (Неотложная медицинская помощь)
Due to the increase in injury rate and increased social activity in pregnant women, there is an increase in the number of abdominal injuries as a result of accidents, domestic conflicts, and abuse. The absence of systematic reviews and meta-analyses related to the algorithmization of treatment tactics for multisystem abdominal trauma leads to a large percentage of treatment and diagnostic errors and complications, high maternal and perinatal mortality, which, in turn, dictates the need to develop a standardized interdisciplinary approach to the management of this category of patients.Aim of study. Standardization of the therapeutic and diagnostic approach to the treatment of pregnant women with multisystem closed abdominal trauma.Material and methods. This literature review presents data from Russian and foreign publications from January 2015 to December 2020 from the electronic databases of PubMed, Cochrane Library, Scopus, eLibrary using the primary search strategy: trauma of pregnant women, multisystem closed abdominal trauma, damage control surgical treatment, emergency caesarean section, post-mortem caesarean section, treatment and diagnostic algorithm, obstetric bleeding, uterine rupture, placental abruption (total 571 publications), with the following exception from the request for non–full-text articles, publications not in Russian or English, manuscripts, dedicated to open trauma and obstetric complications of non-traumatic origin. The data extraction method was performed by two researchers independently of each other. We analyzed multicenter studies, large series of cases, original articles (11 retrospective studies with the selection of patients from 2001 to 2015; all 988 pregnant women with blunt abdominal trauma) and clinical recommendations; systematic reviews, meta-analyses, and randomized clinical studies for this period on multisystem closed trauma in pregnant women were not found. The levels of evidence and strength of recommendations in the review are derived from Russian and foreign clinical recommendations based on meta-analyses and systematic reviews prior to 2015.Results. The treatment and diagnostic algorithm for multisystem abdominal trauma in pregnant women was standardized based on their hemodynamic status, and indications for minimally invasive and open interventions in this category of patients were clarified.Conclusion. Timely diagnosing and multidisciplinary approach contribute to reducing both maternal and perinatal mortality.